Cause-related marketing for disaster risk reduction in the tourism industry: A comparative analysis of prevention- and recovery-related campaigns. (December 2018) - Aliperti, Giuseppe; Rizzi, Francesco; Frey, Marco
Abstract: An increasing number of companies are using Cause-related Marketing (CrM) to fund-raise in support of disaster risk reduction (DRR) activities. This study presents a comparative analysis of two CrM campaigns promoted by a tourism firm in order to improve disaster prevention and recovery of the destination. The results highlight that European tourists belonging to generation Y process prevention- and recovery-related stimuli in different ways. Prevention-related campaigns appear to be generally more effective than recovery-related campaigns. Interestingly, taking in consideration only less-involved to the cause consumers, the intention to participate to the campaign slightly increases in the presence of recovery-related instead of prevention-related cause suggesting further investigation focused on this trend. Theoretical contributions refer to the increased understanding of how tourists elaborate the concept of prevention and recovery from a message framing theory perspective. The paper concludes with managerial implications and opportunities to leverage disaster-oriented CrM campaigns in order to protect hazard-exposed communities.